Collaborative Governance of Tourism Policy of Bali Province, Policy Study based on Local Wisdom Sad Kerthi - Kerti, Maryasih Ni Luh; Effendy, Khasan; Fitriati, Rachma; Faisal, Faisal (Jurnal Manajemen Pelayanan Publik, 2025)
In early 2025, Bali faced a major flood that disrupted tourism activities, followed by a tragedy in Monkey Forest, Ubud, where two foreign tourists died after being struck by a falling tree. These incidents highlight the fragility of Bali’s tourism governance, despite the sector being the backbone of the regional economy. This study analyzes collaborative governance in Bali’s tourism policy with emphasis on integrating Sad Kerthi, the Hindu-Balinese philosophy of environmental and spiritual balance, as outlined in Governor’s Circular No. 4/2022. A qualitative case study was conducted through ten in-depth interviews, three months of field observations (March–June 2024), and policy document analysis, including the RPJPD 2025–2045. Thematic analysis with cross-source triangulation ensured validity. Findings indicate that Sad Kerthi implementation remains largely symbolic. Rituals are regularly performed, yet ecological awareness is weak, pollution and deforestation (46–51 ha/year) persist, and mental health issues are rising. Collaborative forums exist but are still dominated by government actors, limiting genuine participation from customary institutions and communities. The study concludes that cross-sector collaboration, institutional capacity strengthening, and culture-based education are essential to transform Sad Kerthi from a symbolic policy into an operational framework for sustainable tourism governance.